2020
DOI: 10.21203/rs.3.rs-54298/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of comorbidity burden on mortality in patients with COVID-19: a retrospective analysis of the Korean health insurance database

Abstract: We aimed to investigate the impact of comorbidity burden on mortality in patients with COVID-19. We analyzed the COVID-19 data from the nationwide health insurance claims of South Korea. Data on demographic characteristics, comorbidities, and mortality records of patients with COVID-19 were extracted from the database. The odds ratios of mortality according to comorbidities in patients with COVID-19 with and without adjustment for age and sex were calculated. The predictive value of the original Charlson comor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Chronic liver disease, which elevates the risk of death of people with the virus, can also be one of the determinant factors of the final outcome of patients with COVID-19. Several studieshavealso shown thatpeople with liver diseaseare more vulnerable so that liver disease increases the odds of death in contaminated cases (8,16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic liver disease, which elevates the risk of death of people with the virus, can also be one of the determinant factors of the final outcome of patients with COVID-19. Several studieshavealso shown thatpeople with liver diseaseare more vulnerable so that liver disease increases the odds of death in contaminated cases (8,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Co-occurrence of non-communicable diseases such as diabetes, cardiovascular disease, cancer, hypertension, kidney disease, and other chronic diseases is taken as a proven risk factor for increasing risk of acute outcome or even death from COVID-19 (6,7).Treatment of COVID-19 in patients with underlying co-morbidity may be associated with intensive cares and ventilator supports (4).Identifying risk factors for mortality is an important component for COVID-19 management strategies. These evidences are important at a time when demand for intensive care is increasing and resources are limited (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Later, it was shown that people from more deprived social backgrounds and those belonging to ethnic minorities were also at an increased risk. Preexisting medical conditions, such as congestive heart failure, dementia, chronic pulmonary disease, liver or renal disease, and cancer have also been shown to increase the risk (e.g., Cho et al, 2021).…”
Section: Introductionmentioning
confidence: 99%